The global castings industry (overview) - Turner, Andrew (БНТУ, 2017)
A brief analysis of the state of the foundry industry around the world reflecting on political and economic factors that are currently affecting the demand and supply of castings is given. The figures of the global output and break this down into the top producing countries with specific information on the figures and efficiency from these countries are provided. Finally a short discussion on the state of global factors affecting the industry, covering demand drivers and changes in the political and social environment and how these will affect foundry industry in the short and medium future is provided.
Глобальное состояние литейной промышленности (обзор)